Developmental Changes in ANS Precision Across Grades 1–9: Different Patterns of Accuracy and Reaction Time - Malykh, Sergey; Kuzmina, Yulia; Tikhomirova, Tatiana (Frontiers in Psychology, 2021)
The main aim of this study was to analyse the patterns of changes in Approximate Number Sense (ANS) precision from grade 1 (mean age: 7.84 years) to grade 9 (mean age: 15.82 years) in a sample of Russian schoolchildren. To fulfil this aim, the data from a longitudinal study of two cohorts of children were used. The first cohort was assessed at grades 1−5 (elementary school education plus the first year of secondary education), and the second cohort was assessed at grades 5−9 (secondary school education). ANS precision was assessed by accuracy and reaction time (RT) in a nonsymbolic comparison test (“blue-yellow dots” test). The patterns of change were estimated via mixed-effect growth models. The results revealed that in the first cohort, the average accuracy increased from grade 1 to grade 5 following a nonlinear pattern and that the rate of growth slowed after grade 3 (7−9 years old). The nonlinear pattern of changes in the second cohort indicated that accuracy started to increase from grade 7 to grade 9 (13−15 years old), while there were no changes from grade 5 to grade 7. However, the RT in the nonsymbolic comparison test decreased evenly from grade 1 to grade 7 (7–13 years old), and the rate of processing nonsymbolic information tended to stabilize from grade 7 to grade 9. Moreover, the changes in the rate of processing nonsymbolic information were not explained by the changes in general processing speed. The results also demonstrated that accuracy and RT were positively correlated across all grades. These results indicate that accuracy and the rate of nonsymbolic processing reflect two different processes, namely, the maturation and development of a nonsymbolic representation system.